Impact of monocrotophos and its biodegraded metabolites on green gram seed germination and zebra fish embryo development. (January 2021) - Raja prabu, M.; Murugan, A.
Abstract: Impacts of pesticide on soil bacteria, plants and animals have been thought by many people but experimental data are scanty. Present study aimed at assessing the toxicity of monocrotophos on both plant and animal with reference to green gram seed germination and embryo development of zebra fish respectively. 11 different bacteria were isolated from agriculture soil. Among 11 bacterial isolates, isolate AM2 exhibiting better monocrotophos degradation and more tolerance to 300 mg L-1 concentration of monocrotophos and able to degrade completely after 10 days of exposure. Bacterial identification of AM2 using16S rRNA sequence analysis showed that Brevundimonas diminuta . Degradation of Monocrotophos were extracted, separated by thin layer chromatography and confirmed by FTIR analysis. Impact of pesticide and its metabolites on seed germination of Vigna radiata and cytotoxicity among zebra fish embryo tested displayed differently. Seed germination assay demonstrated that monocrotophos had negative effect on the germination of Vigna radiata seeds and degraded metabolites had no effect on seed germination. In Fish embryo toxicity test, monocrotophos causes deformities while development of zebra fish embryo and degraded metabolites of monocrotophos had no negative impacts. Hence B. diminuta has great potential for degradation of monocrotophos and converted from toxic form to non-toxic compounds. Highlights: Soil bacteria able to mellow down the toxicity of monocrotophos by converting in to lesser toxic metabolites. Brevundimonas diminuta reduce monocrotophos toxic effect on seed germination. Also prevent zebra fish embryo development from the contaminated monocrotophos in aquatic environment.